تدبير أذيات النسج الرخوة والغطاء الجلدي في كسور الساق المفتوحة خبرة مشفى الأسد الجامعي باللاذقية 2001-2004 - بطرس, ميشيل; يوسف, صفوان; شرمك, ياسر محمود (Latakia University Journal -Medical Sciences Series, 2019)
تم إجراء الدراسة على 70 مريضا قبلوا بتشخيص كسر ساق مفتوح مع أذية في النسج الرخوة من عام 2001- 2004 حيث أظهرت الدراسة: - سيطرة إصابة الذكور وذلك بنسبة 92،85% ومعظم الإصابات في العقدين الثالث والرابع بنسبة 82،86% -إصابة الطرف السفلي الأيمن أكثر من الأيسر بنسبة 57،14% والثلث المتوسط هو المكان الأكثر إصابة بنسبة 50 % . - السبب الأكثر شيوعاً لحدوث هذه الكسور هو حوادث السير بنسبة 85،71 % . - أكثر أجهزة التثبيت استخداماً كانت أجهزة AO وذلك بنسبة 67,14 % . - أغلب الكسور المفتوحة كانت من الدرجة A III بنسبة 57،15 % -درجةB III بنسبة 7،14 % - درجة CIII بنسبة2,86%- درجة I بنسبة 17،14 % -درجة II بنسبة 15،71 % وذلك حسب تصنيف كاستيلو. - كان استخدام الطعوم الجلدية الحرة كوسيلة لإصلاح عيوب النسج الرخوة والغطاء الجلدي الأكثر شيوعاً بنسبة57،14 %-الشرائح الجلدية الصفاقية من نفس الطرف بنسبة 22,86 % - الشرائح الجلدية المتصالبة بنسبة 17,14 %- وهناك حالتان فقط شفيتا بإجراء خياطة تقريبية بنسبة 2،86 %. The study was carried out on 70 patients who were admitted for open leg fracture diagnosis with injury in the soft tissues(from year 2001 to 2004), it showed : - Male cases prevailed with a percentage of 92.85% and most injuries occurred in the third & fourth decades with a percentage of 82.86% age . -injuries of the right lower limb are more often than the left one with a percentage of 57,14%. and the middle third is the most injured area with a percentage of 50%. -The most common reason for these fractures occurrence is traffic accidents with a percentage of 85,71%. -The most usage of fixation devices was Ao devices with a percentage of 67.14%. -Most open fractures were classified as III A fractures with a percentage of 15,57 %.III B with a percentage of 7,14%, III C with a percentage of 2,86%, I type with a percentage of 17,14%, II type with a percentage of 15,71% according to Castillo classification -The most common treatment was by using the free skin grafts to treatment defects of soft tissues and cover skin with a percentage of 57,14% .Fasciocutaneous flaps at the same limb with a percentage of 22,86%.Fasciocutaneous spica flaps with a percentage of 17,14%. There were only two cases which had been healed by doing proximally sutures with a percentage of 2,86%.